Contactless Finger / Ainun Najhah Mat Saad and Norarifah Ali - Mat Saad, Ainun Najhah; Ali, Norarifah (Faculty of Art and Design, 2021)
When in a public place many people will touch the surface. For example, ATM machine buttons, elevator buttons and other related buttons. Other people may become infected by touching these objects or surfaces, then touching their eyes, noses or mouths before cleaning their hands. This is why it is essential to thoroughly clean hands regularly with soap and water or use an alcohol-based hand rub product, and to clean the surfaces regularly. Coronavirus disease (COVID-19) is an infectious disease. Most people who are infected with COVID-19 will experience mild to moderate symptoms and recover without special treatment. People with the virus in their noses and throats may leave infected droplets on objects and surfaces (called fomites) when they sneeze, cough on, or touch surfaces. For example, the ATM button or the elevator button that is always being touched. Various people touch the buttons without wearing finger protectors. From these surfaces they can be infected with Covid 19. Some people wear gloves and they neglect to practice hand hygiene, because they think that their hands are already clean.